(untitled) (Experimental biology, 2025)
Many hundreds of exotic species and domestic animal breeds have been lost over the course of the last few decades. Therefore, it is very important to develop and apply rescue strategies to ensure the other animals threatened with extinction to ensure their survival for the future. One way to protect the endangered species of wild and domestic animals is to the creation of cryobanks of their gametes. The purpose of this review is to provide new data on the methods of cryopreservation of the gametes and gonads of dogs (Canis lupus familiaris). Here we consider the types of cryopreservation that affect the structure of these cells and tissues during cryopreservation, as well as functional disorders of cells from the effects of damage and strategic ways to protect them will be discussed. Differences and similarities between single cell or tissue cryopreservation will be highlighted, together with the evidence and basic principles of choosing a particular type of cryopreservation. The analysis of different aspects that still hamper the success of cryopreservation these animals’ cells can help clarify where research is most needed. The date provided, in turn, can contribute to the development of effective solutions to these methods in the future.